A study of security system in public higher education institution in Klang Valley / Ahmad Subaih Md Junus - Md Junus, Ahmad Subaih (2012)
This dissertation focuses on user perception of the security system in higher education institution. This subject has rarely been explored in the past maybe due to the fact that people do not see it has as that important. Security system has been installed at every location imaginable. The security awareness has only consolidated the fact that security systems are very important systems and has to be looked into seriously by those people involved in the construction industry. The objective of the study is to get some insight on what security means, the concept of security and the types of system. From the research which has been done, the security systems which are commonly used in public higher educational institutions is an active security and passive security system. To support this research questionnaire was used as a method to determine the effectiveness and performance of the security system in the higher public education institution. The author hopes that this research will throw in some light in some light on the various aspects of security systems and the bright it holds. It is also hoped that this research will stir more people to explore and focus on the various aspects of security systems in greater depth.